2020
DOI: 10.1089/jmf.2019.4651
|View full text |Cite
|
Sign up to set email alerts
|

High-Fat Diet Increases Fat Oxidation and Promotes Skeletal Muscle Fatty Acid Transporter Expression in Exercise-Trained Mice

Abstract: The aim of this study was to investigate the effect of a high-fat diet (HFD) on energy substrate utilization during long-term endurance exercise in mice. Male ICR mice (n = 32; 6 weeks old) were divided into two groups: low-fat diet (LFD, n = 16) and HFD (n = 16) and acclimatized to LFD or HFD feeding over 12 weeks. After 12 weeks, the two dietary groups were each divided into two groups with or without exercise (EX): LF-CON, LF-EX, HF-CON, and HF-EX groups. The exercise groups were trained to run on a treadmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…In our study, in the HFD (+GPAT) muscle, the content of FA transporters CD36 and FABPpm significantly increased, as compared to the control, and, in the muscles with HFD (-GPAT) , we observed a decrease in the level of all examined FA transporters compared to muscles with HFD (+GPAT) . The increased content of FA transporters in the skeletal muscles of HFD-fed or obese mice was also previously repeatedly presented by other researchers [ 27 , 28 , 29 ]. GPAT is an enzyme that participates in the synthesis of DAG and, because DAG is an intermediate in de novo TAG synthesis, GPAT also participates in the synthesis of TAG.…”
Section: Discussionsupporting
confidence: 75%
“…In our study, in the HFD (+GPAT) muscle, the content of FA transporters CD36 and FABPpm significantly increased, as compared to the control, and, in the muscles with HFD (-GPAT) , we observed a decrease in the level of all examined FA transporters compared to muscles with HFD (+GPAT) . The increased content of FA transporters in the skeletal muscles of HFD-fed or obese mice was also previously repeatedly presented by other researchers [ 27 , 28 , 29 ]. GPAT is an enzyme that participates in the synthesis of DAG and, because DAG is an intermediate in de novo TAG synthesis, GPAT also participates in the synthesis of TAG.…”
Section: Discussionsupporting
confidence: 75%
“…In the studies conducted here, we also found that the elevated plasma FFA concentration was accompanied by an increase in the level of the proteins CD36, FATP1 and FABPpm involved in the transport of fatty acids in skeletal muscles. The same results were obtained by Yun et al [ 46 ] and other researchers [ 47 , 48 , 49 ]. They confirmed the effect of a HFD on an increase of fatty acid transporter expression.…”
Section: Discussionsupporting
confidence: 89%
“…High-fat diet (HFD) is associated with increased disease severity of both MS and EAE by changes in metabolism, inflammation and oxidative stress 26 . Specifically HFD has been found to upregulate CPT1A lipid metabolism 29 . Therefore, we investigated the effect of HFD in the EAE model using female Cpt1a and WT mice (Fig.…”
Section: Resultsmentioning
confidence: 99%